The role of the audiovisual authority in regulating the media sector: Between the legal text and application - Bouslama, Hanene (Journal of Human Sciences, 2022)
The Algerian Regislator created an audiovisual control authority for the first time under the organic law 12-05 pertinent to the media in which it was regulated by law 14-04 related to audiovisual activity in which it was expressly provided for its enjoyment of legal personality and financial autonomy. Also, the article 54 of the same law stipulates the powers granted to this authority so that it can actually perform it’s tasks, although these powers are remained limited and restricted because they are under government guardianship.